Racial/Ethnic and social class differences in preventive care practices among persons with diabetes - Oladele, Carol R Williams (BioMed Central, 2006)
BACKGROUND: Diabetes is the sixth leading cause of death in the United States. Persons with diabetes are at increased risk for serious complications including CVD, stroke, retinopathy, amputation, and nephropathy. Minorities have the highest incidence and prevalence of diabetes and related complications compared to other racial groups. Preventive care practices such as smoking cessation, eye examinations, feet examinations, and yearly checkups can prevent or delay the incidence and progression of diabetes related complications. The purpose of this study was to examine racial/ethnic differences in diabetes preventive care practices by several socio-demographic characteristics including social class. METHODS: Data from the Behavioral Risk Factor Surveillance Survey for 1998–2001 were used for analyses. The study population consisted of persons who indicated having diabetes on the BRFSS, 35 yrs and older, and Non-Hispanic Black, non-Hispanic White, or Hispanic persons. Logistic regression was used in analyses. RESULTS: Contrary to our hypotheses, Blacks and Hispanics engaged in preventive care more frequently than Whites. Whites were less likely to have seen a doctor in the previous year, less likely to have had a foot exam, more likely to smoke, and less likely to have attempted smoking cessation. Persons of lower social class were at greatest risk for not receiving preventive care regardless of race/ethnicity. Persons with no health care coverage were twice as likely to have not visited the doctor in the previous year and twice as likely to have not had an eye exam, 1.5 times more likely to have not had a foot exam or attempted smoking cessation. CONCLUSION: This study showed that persons of lower social class and persons with no health insurance are at greatest risk for not receiving preventive services.